Gaming and the divine: a new systematic theology of video games - Bosman, Frank (Routledge new critical thinking in religion, theology, and biblical studies, 2019)
Fundamentals I: a theology of culture -- Fundamentals II: a study of games -- Theomorphism: creational theology -- Christophorism: Christology -- Homo Roboticus: theological anthropology -- Kyrie Eleison: theodicy and the problem of evil -- The wicked problem of being alive: ethics -- Game over: Thanatology -- God's delusion: religion critique in video games -- A systematic theology of video games.